MEDIA PEMBELAJARAN INOVASI TEKNOLOGI MENGGUNAKAN APLIKASI QUIPPER SCHOOL DI MAN 1 MOJOKERTO - Bani Munir, Muhammad Rasyid Ridho Al Falaqi; Irma Soraya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
In this research, a qualitative descriptive approach was used in this research method, which can be interpreted as an approach that interprets and describes the information obtained according to field conditions and cannot be achieved using statistical methods or quantification methods. The use of online learning can facilitate interaction between teachers and students or fellow students, as well as making it easier to place learning materials and student assignments at the teacher's location specified in the applications available to students. Teachers can use many web-based learning media applications, including the Quipper School application. Quipper School is an online application that can be a learning tool between teachers and students. This application has features that can help teachers in the teaching and learning process and achieve the learning goals themselves. This application helps make learning problems that were previously monotonous interesting and not boring for students and students can become active.